Agronomic evaluation of introduced accessions of Vicia narbonensis L. under contrasting environments and two years period - Zoghlami Khélil A.; Hassen H.; Ben Salem H.; Ben Youssef S. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
This work aimed to evaluate agronomic and nutritive characteristics of 9 accessions of Vicia narbnonensis received from ICARDA under the framework of germoplasm exchange. They were evaluated in two contrasting locations (Oued Mliz, semi arid and Oued Béja, sub humid) during two cropping years (2009-2010 and 2010-2011) in comparison with two checks arranged in a randomised complete bloc design with three replications. Seed yields, pod and seed number, flowering date and winter vigour were scored. During first year, analysis of variance showed significant effects of site, accession and their interaction for all agronomic traits. Flowering and pod set are earlier in Oued Mliz while pod maturity was earlier in Oued Béja with highest number of pods. Seed number and seed weight were higher in Oued Mliz. Significant correlations were obtained between flowering and pod set and flowering and pods/plant. Among these accessions, 6 were selected and evaluated the following year. During second year, seed yield of these accessions was two times higher in Oued Béja. Based on yield and yield components, two accessions were released for cultivars registration.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)